Challenges faced by blind patients using chronic medication at a tertiary hospital in South Africa - Madan S. Poka; Jonathan T. Chanyandura; Bwalya A. Witika (AOSIS, 2022)
Background: Difficulties faced by blind patients in using medicines are largely unknown and underexplored. This limits the ability of health providers and health policy makers to plan and provide for medicine related needs of this special group. Objectives: To describe the challenges faced by blind patients around Mankweng Hospital when taking chronic medications and to identify methods used to overcome the challenges. Methods: Quantitative cross-sectional descriptive study, where questionnaires were administered to 82 blind patients, 18 years and older, and who were on chronic medications. Data was analysed using the Statistical Package for the Social Sciences (SPSS) software. Results: Majority of participants were elderly (59%) and had partial blindness (78%). Challenges faced by participants included inability to locate and identify medication (60%), missing doses (64%), inaccurate dosing and spilling medicines (33%). A staggering 68.3% of the participants did not have specific methods to overcome challenges. Conclusions: Challenges faced by the blind and visually impaired are similar across the world. However, participants are unaware of other simple, feasible methods available in the market. Current methods used by the participants to overcome the challenges encountered are minimal or caregiver dependent. Programs may be set up at clinics, hospitals and health care centers to teach the visually impaired simple and inexpensive methods to help administer medications. Contribution: Results obtained may be used to raise awareness in health care policy makers of the under-explored challenges faced by the partially blind or completely blind patients in the use of medicines.